2019
DOI: 10.29313/gmhc.v7i2.4149
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Intra-familial Hepatitis B Virus Transmission among Hepatitis B Patients in Kupang, Indonesia

Abstract: Hepatitis B is caused by acute or chronic hepatitis B virus infection. It is the most dangerous liver disease compared to other liver diseases due to its lack of apparent symptoms. The symptoms include slight jaundice in the eyes and skin accompanied by lethargy. This study aimed to determine the risk factors for intra-familial transmission of hepatitis B virus for household contacts of hepatitis B patients. The analytical correlation study with a cross-sectional design was conducted from June to July 2018 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…30,31 In this study, HBsAg positivity in household contacts was 14.7%, confirming previous studies' results of high HBsAg prevalence in household contacts in Kupang. 15 The percentage of positive HBsAg in healthcare workers in Kupang was significantly high at 16.9%. As one of the high-risk population groups for HBV transmission, there is still no mandatory hepatitis B immunization program for healthcare workers in Indonesia.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…30,31 In this study, HBsAg positivity in household contacts was 14.7%, confirming previous studies' results of high HBsAg prevalence in household contacts in Kupang. 15 The percentage of positive HBsAg in healthcare workers in Kupang was significantly high at 16.9%. As one of the high-risk population groups for HBV transmission, there is still no mandatory hepatitis B immunization program for healthcare workers in Indonesia.…”
Section: Discussionmentioning
confidence: 92%
“…22,23 Household contact with hepatitis B patients was also considered a high-risk population as they frequently share household items like razors, plates, cutlery, glassware, face towels, and toothbrushes. 15,29 Previous studies in several Asian countries have shown that the potential of HBV transmission from hepatitis B patients to those living in the same household is high. Especially for parents, siblings, or other household residents who were in close contact, share household items, have poor personal hygiene habits, and have previous blood transfusion history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk for HBV infection in the seasonal migration group was 4.3 times higher compared to local workers (p=0.00; OR=4.3; 95% CI=2.2-8.4), with a prevalence rate of 11%. 18 The importance of the HBV screening test of pregnant women was also carried out by Yi et al 19 and Kambuno et al 20 Their study suggested screening pregnant women to find out whether they are infected with hepatitis B. Early immunization of babies born to women infected with hepatitis B is highly recommended, and check HbsAg for those women going to marry.…”
Section: Discussionmentioning
confidence: 99%
“…Penularan horizontal VHB dapat terjadi melalui berbagai cara yaitu penularan perkutan, melalui selaput lendir atau mukosa (Pusparini & Ayu, 2017). Hepatitis B dapat menyerang dengan atau tanpa gejala Hepatitis (Kambuno, Bessie, Tangkelangi, & Djuma, 2019). Pada kehamilan, risiko terinfeksi virus HBV sebenarnya sama dengan wanita tidak hamil di usia yang sama dan dapat timbul di ketiga trimester kehamilan.…”
Section: Pendahuluanunclassified